VTA-NAc glutaminergic projection involves in the regulation of pain and pain-related anxiety - Abdul, Mannan; Yan, Hao-Qi; Zhao, Wei-Nan; Lyu, Xiao-Bin; Xu, Zheng; Yu, Xiao-Lu; Gao, Yi-Hong; Cao, Jun-Li (Frontiers in Molecular Neuroscience, 2022)
Background Besides the established role of dopamine neurons and projections in nociceptive stimuli, the involvement of ventral tegmental area (VTA) glutamatergic projections to nucleus accumbens (NAc) in pain remains unknown. In the present study, we aimed to examine the role of VTA glutamatergic projections to NAc in painful stimuli and its related behavioral changes. Methods Unilateral chronic constrictive injury (CCI) of sciatic nerve or intraplantar hind paw injections (i.pl.) of complete Freund’s adjuvant (CFA) were used to develop pathological pain models in wild-type and VGluT2-Cre mice. The involvement of VTA glutamatergic neurons with projections to NAc in CCI-induced pain model was noted by c-Fos labeling and firing rate recordings. Pain response and pain-related behavior changes to the artificial manipulation of the VTA glutamatergic projections to NAc were observed by Hargreaves tests, von Frey tests, open field tests, elevated maze tests, and sucrose preference tests. Results Glutamatergic neurons in VTA had efferent inputs to shell area of the NAc. The CCI pain model significantly increased neuronal activity and firing rate in VTA glutamate neurons with projections to NAc. The photoinhibition of these glutamatergic projections relieved CCI-induced neuropathic pain and CFA-induced acute and chronic inflammatory pain. Moreover, pathological neuropathic pain-induced anxiety and less sucrose preference were also relieved by inhibiting the VTA glutamatergic projections to NAc. Conclusion Together, glutamatergic inputs from VTA to NAc contribute to chronic neuropathic and inflammatory pain and pain-related anxiety and depressive behaviors, providing a mechanism for developing novel therapeutic methods.